CACNA1A Gene Variants in Eight Chinese Patients With a Wide Range of Phenotypes - Zhang, Linxia; Wen, Yongxin; Zhang, Qingping; Chen, Yan; Wang, Jiaping; Shi, Kaili; Du, Lijun; Bao, Xinhua (Frontiers in Pediatrics, 2020)
Background: The CACNA1A gene encodes the voltage-dependent P/Q-type calcium channel subunit alpha-1A, which is widely expressed throughout the CNS. The biological roles of the P/Q channel are diverse and the phenotypic spectrum caused by CACNA1A mutations is wide. The aim of this study is to demonstrate its phenotypic diversity and analyze the genotype-phenotype correlations in a cohort of Chinese patients. Methods: Patients with hemiplegic migraine, cerebellar ataxia, developmental delay, or epilepsy without known causes were tested by trios whole-exome sequencing. Patients with pathogenic CACNA1A gene variants were recruited. The clinical information of the patients was collected, and the association between the genotype and the phenotype was investigated. Results: In total, eight patients (six females and two males) were found to have CACNA1A gene variants. All the variants were de novo including six missense variants and one frameshift variant. Four de novo missense variants were found in five patients located in the S4, S5, or S6 transmembrane segments of Domain II and III (p.R1352Q, p.G701V, p.A713T, p.V1393M). All of them were correlated with severe phenotypes, including three with sporadic hemiplegic migraine type 1 and epilepsy, and two with developmental and epileptic encephalopathy. The other two missense variants, p.Y62C and p.F1814L, located in the cytoplasmic side of the N-terminus and C-terminus, respectively. The variant p.Y62C was associated with severe hemiconvulsion-hemiplegia-epilepsy syndrome, and p.F1814L was associated with relatively mild phenotypes. All the missense variants were speculated as gain-of-function (GOF) mutations. The only frameshift variant, p.Q681Rfs*100, a lose-of-function (LOF) mutation, was found in a patient with episodic ataxia type 2. Meanwhile, all the patients had developmental delay ranging from mild to severe, as well as cerebellar ataxia including one with congenital ataxia, one with episodic ataxia, and six with non-progressive ataxia. Conclusions:CACNA1A variants could lead to a wide spectrum of neurological disorders including epileptic or non-epileptic paroxysmal events, cerebellar ataxia, and developmental delay. The variants could be both GOF and LOF mutations. There appeared to be some correlations between genotypes and phenotypes.